Belirgin kardiyovasküler hastalığı olmayan hastalarda COVID-19 mRNA aşısının elektrokar-diyografik parametreler üzerinde herhangi bir etkisi var mı? - KEPEZ, ALPER; TİGEN, ELİF (My University, 2022)
Objective: Electrocardiographic alterations were investigated following the second dosage of COVID-19 mRNA vaccination. Methods: A total of 260 individuals after two doses of COVID-19 vaccine with Pfizer-BioNTech were included in the study. The electrocardiographic parameters recorded at baseline and approximately one week later after two doses of Pfizer-BioNTech vaccine were compared for all patients. Results: PR interval was increased and QTc maximum interval was decreased significantly after second dose COVID-19 mRNA vaccination. Baseline and post-second dose vaccination states regarding P wave dispersion and QT dispersion/Tp-e interval which have been recognized to imply inhomogeneous atrial conduction and heterogeneity in ventricular repolarization were similar between groups. Conclusion: Our findings suggest that there should be no concern related to asymptomatic involvement of the myocardium subsequent the second dose of COVID-19 mRNA vaccination.
Keywords: Tıp; Dahili Tıp Bilimleri; Kardiyoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Cardiovascular; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CARDIAC ve CARDIOVASCULAR SİSTEMLER; TIP, GENEL & İÇECEK; Clinical Medicine (MED); CLINICAL MEDICINE; CARDIAC & CARDIOVASCULAR SYSTEMS; MEDICINE, GENERAL & INTERNAL; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Kardiyoloji ve Kardiyovasküler Tıp; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Cardiology and Cardiovascular Medicine; Medicine (miscellaneous); General Medicine; COVID-19; mRNA vaccine; myocarditis; electrocardiography; P wave dispersion; QT dispersion; mRNA aşısı; miyokardit; elektrokardiyografi; P dalga dispersiyonu; QT dispersiyonu